Children like dense neighborhoods: orthographic neighbourhood density effects in novel readers - Duñabeitia, Jon Andoni; Vidal-abarca, Eduardo (The Spanish Journal of Psychology, 2008)
Previous evidence with English beginning readers suggests that some orthographic effects, such as the orthographic neighborhood density effects, could be stronger for children than for adults. Particularly, children respond more accurately to words with many orthographic neighbors than to words with few neighbors. The magnitude of the effects for children is much higher than for adults, and some researchers have proposed that these effects could be progressively modulated according to reading expertise. The present paper explores in depth how children from 1st to 6th grade perform a lexical decision with words that are from dense or sparse orthographic neighborhoods, attending not only to accuracy measures, but also to response latencies, through a computer-controlled task. Our results reveal that children (like adults) show clear neighborhood density effects, and that these effects do not seem to depend on reading expertise. Contrarily to previous claims, the present work shows that orthographic neighborhood effects are not progressively modulated by reading skill. Further, these data strongly support the idea of a general language-independent preference for using the lexical route instead of grapheme-to-phoneme conversions, even in beginning readers. The implications of these results for developmental models in reading and for models in visual word recognition and orthographic encoding are discussed.